(untitled) (Prilozi za orijentalnu filologiju, 2024)
In this paper, we write about the oldest Ottoman documents (berats, firmans, buyuruldis and tezkiras) from the Collection of Gifts and Redemptions of the Archives of Bosnia and Herzegovina, which talk about the allocation of land holdings (timars) and appointments to military duties. Along with the presentation and analysis of the amount of military salaries and income over the centuries, we tried to approximate the value of land holdings and military salaries in this period.